On the Origin of Shame: Does Shame Emerge From an Evolved Disease-Avoidance Architecture? - Terrizzi Jr., John A.; Shook, Natalie J. (Frontiers in Behavioral Neuroscience, 2020)
Shame and disgust are believed to be evolved psychological solutions to different adaptive challenges. Shame is thought to promote the maintenance of social hierarchies (Gilbert, 1997; Fessler, 2004), whereas disgust is believed to encourage disease avoidance (Curtis et al., 2004; Oaten et al., 2009). Although shame and disgust are often treated as orthogonal emotions, they share some important similarities. Both involve bodily concerns, are described as moral emotions, and encourage avoidance of social interaction. The purpose of the current research was to examine whether shame is uniquely related to disgust and pathogen avoidance. To rule out an association due to the negative valence of both emotions, guilt was also examined. In Study 1, disgust sensitivity and fear of contamination were positively correlated with shame, but not guilt, even after controlling for negative affect. In Study 2, a disgust induction increased shame, but not guilt, for individuals who were sensitive to disgust. The current research provides preliminary evidence for a unique relation between shame and disgust.